Students’ Well-Being and Game Implementation in Learning Chemistry in Merdeka Belajar Era - Ni'matul Zahro; Achmad Lutfi (Universitas Pendidikan Ganesha, 2021)
Students' well-being takes a primary role. Innovation to enhance students' well-being is game implementation as learning media. This research aims to discover students' well-being consequences on students’ academic performance in learning chemistry in Merdeka Belajar era, know students’ academic performance enhancement after game implementation as learning media in Merdeka Belajar era, and know students’ responses in games implementation as learning media in Merdeka Belajar era. This study uses One Group Pretest-Posttest Design with 33 XI-MIA students at high school as a research subject. Instruments used in this study were student well-being questionnaire, student pretest-posttest sheets, and student response questionnaire. Student well-being questionnaires result before and after game implementation was tested correlation resulting significance value 0.043 and correlation coefficient 0.36. The pretest and posttest students' outcomes were tested by paired sample T-test significance 5% resulting significance value 0.002. The students' responses result is ≥ 60% in agreement. Then it can be summed up that implementation of the game as a learning media can develop the well-being of students.